Implementasi Kebijakan Pengembangan Pariwisata Berkelanjutan Dalam Meningkatkan Perekonomian Daerah di Provinsi Banten - julizar Idris; Jumanah Jumanah; Alfatimatun Shiva Bella; Diva Febiyanti; M.Angga Rahmadani; Sritevi Wahyuni (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
economy in Banten Province. Tourism has become an important driver of regional economic growth because it generates multiplier effects through employment creation, micro, small, and medium enterprise development, local product demand, and regional revenue generation. However, increasing tourist mobility after the pandemic has also created several challenges, including visitor concentration in particular destinations, environmental pressure, limited waste management capacity, and unstable community income caused by seasonal tourism patterns. This study employed a qualitative descriptive approach through a literature review of 30 scientific articles, consisting of 20 international and 10 national publications, supported by relevant policy documents. The analysis focused on tourism governance, local economic development, environmental sustainability, and community participation. The findings show that sustainable tourism development requires a shift from fragmented destination management towards collaborative governance based on the Pentahelix approach and Community-Based Tourism. Strengthening local supply chains, supporting micro, small, and medium enterprises, diversifying tourism products, and improving digital tourism services are important strategies for extending visitor stays and maintaining demand throughout the year. In addition, integrating Sustainable Development Goals principles, environmental carrying capacity, transparent destination governance, and local regulatory support is essential to protect ecosystems and ensure a more equitable distribution of tourism benefits. The study concludes that integrated, participatory, and environmentally responsible tourism policy is necessary to strengthen regional economic resilience and sustainability in Banten Province.